1688 Hospital@Home - An Innovative Cost Effective Approach to Paediatric Care in Community. (October 2012) - Jyothi, S; Vasudevan, A; Hubbard, M; Morris, C; Yuvaraj, V
Abstract : Background: A survey in 2009–10 in our region showed 60% of the total 5500 admissions were discharged from paediatric admissions unit within 4 hours with no active clinical intervention. In early 2011 Local Health Economy(LHE)group consisting of GPs and Paediatricians devised an innovative approach for existing H@H team to manage children with acute illnesses at home and prevent hospital attendance. Aims: To prevent unnecessary hospital attendances and offer a safe cost-effective alternative to short stay admissions by providing clinical care for children at home. Methods: The new H@H service was promoted by GP practice visits and various educational events by the team before commencing in April 2011. Following assessment by GPs, children who needed observation for their acute illnesses and were appropriate to be managed at home were referred to H@H. The H@H team followed local guidelines for management of these children at home and any deterioration in the clinical condition prompted referral to the PAU. Results: Until now H@H has been utilised by 90 of 100 GP practices in our region. 950 children were referred and managed by H@H with no adverse events till date. H@H has crossed the conservative cost effective target of reducing 4 PAU referrals each day with a projected saving of £181, 000/annum. The feedback has been positive from all service users. Conclusions: The two streams of H@H early discharge facility cost-effective admission avoidance facility have proved successful in our region and is currently being evaluated to be introduced by other regions.